Roofscape design : regenerating the city upon the city - Ambrosini, Gustavo; Callegari, Guido (JOVIS Verlag GmbH, 2021)
As focus shifts to "no net land take" city regeneration approaches one of the main traditional elements of architecture-the roof-is gaining renewed prominence. This book provides a survey of worldwide experiences of city rooftop re-use strategies such as building-on and integrating new volumes within the existing buildings. Twenty-five case studies illustrate a multiplicity of projects that innovate on traditional typologies by offering multiple ways of living, working and using public services in the city. They all share a symbiotic method that exploits the extraordinariness of the "top condition" offered by the roof to foster a subtle change in the whole building's urban identity. They test new technologies for light and quick construction methods in order to deal with structural constraints and the needs of inhabitants. City roofscape redesign belongs to an adaptive attitude based on knowledge of the dynamic process of transformation of the physical realm, far removed from regressive preservation-only behavior. It represents a remarkable way of coping with urban regeneration issues.